Medios audiovisuales y su influencia en el conocimiento ambiental de estudiantes del 5to de secundaria (IEPSM) N° 60027 Santa Clara de Nanay 2025 - Solano Gonzales, Vany Lizbet (2025)
The rehearsal was developed in the atmospheres of the Educational Center 60027, of the populated center Santa Clara, the purpose was to evaluate if the audiovisual tools motivate in the student body bigger learning with respect to environmental topics, the work was descriptive observational, the universe conformed it the students of the 5to of secondary session TO (35 students of both sexes), the obtained data of the interviews were processed in SPSS and leaf of calculation Excel, ending up concluding: according to the part cognitive these tools would be an alternative as 28 students they mention it (80%), motivating to the (100%) to treat more topics related with the atmosphere, the contact with the nature is fundamental 30 students mention this way it (85.7%) and not to contaminate the nature (100%), he/she lacks to have more conscience of the environmental deterioration (77%), the courses CTA should treat more envelope these topics and the (54.3%) recyclable material reutilizing, the (100%) they are aware of the importance of the water. The work also reflects that the students need to play more topics on the environmental part (100%) in the course of (CTA) and to develop practical of reutilization of recyclable materials (100%). The Audiovisual tools at the present time are key in the development of people for what the Education cannot be left behind since of these technological advances demonstrate that they help to improve the teaching-learning process in the students.